Identification of non-classical hCA XII inhibitors using combination of computational approaches for drug design and discovery - Al-Sanea, Mohammad M.; Chilingaryan, Garri; Abelyan, Narek; Arakelov, Grigor; Sahakyan, Harutyun; Arakelov, Vahram G.; Nazaryan, Karen; Hussein, Shaimaa; Alazmi, Gharam M.; Alsharari, Haifa E.; Al-faraj, Waad M.; Alruwaili, Faten S.; et al. (Scientific reports, 2021)
Human carbonic anhydrase XII (hCA XII) isozyme is of high therapeutic value as a pharmacological target and biomarker for different types of cancer. The hCA XII is one of the crucial effectors that regulates extracellular and intracellular pH and affects cancer cell proliferation, invasion, growth and metastasis. Despite the fact that interaction features of hCAs inhibitors with the catalytic site of the enzyme are well described, lack in the selectivity of the traditional hCA inhibitors based on the sulfonamide group or related motifs is an urgent issue. Moreover, drugs containing sulfanomides can cause sulfa allergies. Thus, identification of novel non-classical inhibitors of hCA XII is of high priority and is currently the subject of a vast field of study. This study was devoted to the identification of novel potential hCA XII inhibitors using comprehensive set of computational approaches for drug design discovery: generation and validation of structure- and ligand-based pharmacophore models, molecular docking, re-scoring of virtual screening results with MMGBSA, molecular dynamics simulations, etc. As the results of the study several compounds with alternative to classical inhibitors chemical scaffolds, in particular one of coumarins derivative, have been identified and are of high interest as potential non-classical hCA XII inhibitors.